Blood–Brain Barrier Disruption as a Potential Target for Therapy in Posterior Reversible Encephalopathy Syndrome: Evidence From Multimodal MRI in Rats - Wang, Quanlai; Huang, Bin; Shen, Guiquan; Zeng, Yu; Chen, Zheng; Lu, Chunqiang; Lerner, Alexander; Gao, Bo (Frontiers in Neurology, 2019)
Background: To explore blood–brain barrier disruption in hypertensive posterior reversible encephalopathy syndrome. Methods: The hypertension rat models were successfully established and scanned on 7T micro-MRI. MRI parameter maps including apparent diffusion coefficient, T1 value, and perfusion metrics such as cerebral blood volume, cerebral blood flow, mean transit time and time to peak maps, were calculated. Results: The ADC values of the experimental group were higher than those of the control group both in cortical (P < 0.01) and subcortical (P < 0.05) regions. Voxel-wise analysis of ADC maps localized vasogenic edema primarily to the posterior portion of the brain. The increase in cerebral blood volume and cerebral blood flow values were found in the cortical and subcortical regions of rats with acute hypertension. No correlation was found between perfusion metrics and mean arterial pressure. The Evans blue dye content was higher in the posterior brain region than the anterior one (P < 0.05). Conclusions: Cerebral vasogenic edema resulting from acute hypertension supports the hypothesis of posterior reversible encephalopathy syndrome as the result of blood–brain barrier disruption, which maybe the potential therapeutic target for intervention.